High frequency Alternating Current (AC) tangent delta - Shafi, Huzainie; Avinash Raj, Avinash Raj; S. Balasubramaniam, Yogendra (Penerbit UTHM, 2020)
Power cables are constantly subjected to thermal, electrical and mechanical stresses during their service life which leads to ageing of the insulation material. Ageing of the insulation means that the insulator degrades or gets older. When the insulation is degraded it does not have the same physical properties as compared to the new cables, which basically means that the risk of failure has been increased. So, it is necessary to carry out a diagnostic test to resolve the possible problem that may occur in cable insulation so that precautionary action can be taken to avoid unnecessary in-service failure of the underground cable [1]. Dissipation factor or tangent delta measurement in either time or frequency domain are used to identify water tree degraded XLPE cables with high moisture content or moisture ingression through poor jointing, diagnostic tests based on [2], [3]. In practice, standard laboratory electrical test equipment utilizing power frequency (PF) i.e. 50Hz to 60Hz testing is used. Hence, large static transformer was installed in the laboratory to cater any large capacitance test sample for high voltage testing. These existing tangent delta diagnostic test methods are bulk assessment technique that cannot sectionalize or pin point the water tree or any other conductive defect. In addition, both this tangent delta measurement technique which utilizes standard 0.1Hz and 50Hz equipment is not capable to extract the tangent delta values of accessories from the bulk assessment. It can only diagnose the overall condition of the complete cable system that includes cable, joints and terminations. Since medium voltage underground (MVUG) cables in utilities are in service for many years, it is crucial to develop a method to sectionalize or identify the defective components.